The Flaw of Lazyness and its Ideological Repercussions in the Poema de Alfonso Onceno - Erica Janin (Medievalia, 2020)
This study seeks to prove that the characterisation of the Muslim foe’s laziness portrayed in the Poema de Alfonso Onceno’s should not be conceived as a part of a neutral descriptive procedure. On the contrary, it should be understood as a political and ideological tool that seeks to delimit the field of foes and allys —even within the christian faction—, in order to justify a series of actions of promotion or reprobation towards each of the social groups that coexist in the poem.